2018
DOI: 10.46586/tches.v2018.i3.89-120
|View full text |Cite
|
Sign up to set email alerts
|

Composable Masking Schemes in the Presence of Physical Defaults & the Robust Probing Model

Abstract: Composability and robustness against physical defaults (e.g., glitches) are two highly desirable properties for secure implementations of masking schemes. While tools exist to guarantee them separately, no current formalism enables their joint investigation. In this paper, we solve this issue by introducing a new model, the robust probing model, that is naturally suited to capture the combination of these properties. We first motivate this formalism by analyzing the excellent robustness and low randomness requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…This section considers known physical effects which affect the probing security of an implementation and invalidate the separate wire leakage assumption. These effects were already discussed considering the circuit model in the work by Faust et al [14]. However, this section adopts their arguments and discusses the physical effects in the tile probing model instead.…”
Section: The Tile Probing Model Against Advanced Probing Attacksmentioning
confidence: 98%
See 2 more Smart Citations
“…This section considers known physical effects which affect the probing security of an implementation and invalidate the separate wire leakage assumption. These effects were already discussed considering the circuit model in the work by Faust et al [14]. However, this section adopts their arguments and discusses the physical effects in the tile probing model instead.…”
Section: The Tile Probing Model Against Advanced Probing Attacksmentioning
confidence: 98%
“…It is shown that the model captures the effects of area-extended faults as well as faults targeting a specific resource throughout the computation. Moreover, to the best of our knowledge, the model is currently the only one capable of capturing all the physical effects described by Faust et al [14]. Finally, recent introduced attacks such as Statistical Ineffective Fault Attacks (SIFA) and combined attacks, combining both side-channel analysis and fault analysis, are also covered by the model.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To give security proofs, we need to have a security model. Since we are interested in the security of hardware implementations, we make use of the glitch-robust probing model from [10]. A probing adversary chooses up to a threshold number of wires of the algorithm's circuit representation to read the value from (probing).…”
Section: First-order Probing Securitymentioning
confidence: 99%
“…When considering the effect of glitches, with each probe the adversary can read all the input values which flow to that wire until a register is reached. The interested reader is encouraged to learn more about this model in [10], a comparison of the probing model with other leakage models is given in [13], and the proof of the reduction of the noisy leakage model to the probing model is found in [9]. In threshold circuits, the glitch-robust adversary transforms into an adversary reading the circuit's component functions due to the component functions being walled-off by registers.…”
Section: First-order Probing Securitymentioning
confidence: 99%